The double-edged sword effect of agricultural technological progress on agricultural carbon emissions: empirical evidence from China - Zhu, Shiying; Li, Yansong; Wang, Siqi; Liu, Jianxu; Cui, Jiande; Yamaka, Woraphon (Frontiers in Sustainable Food Systems, 2024)
Global climate change has intensified pressure on China's agricultural carbon emissions reduction. This study investigates the impact of agricultural technological progress on carbon emissions using panel data from 30 Chinese provinces (2002–2021). The research employs the DEA-Malmquist index to measure agricultural total factor productivity, the emission factor method to calculate carbon emissions, and two-tier stochastic frontier models for analysis. Results reveal that agricultural technological progress exhibits a significant double-edged effect on carbon emission intensity, with a positive effect increasing intensity by 9.01% and a negative effect reducing it by 12.18%, resulting in a net reduction of 3.17%. Different technological types show varying impacts: mechanical progress increases emission intensity, while resource-saving and biochemical technologies reduce it. Notable regional heterogeneity exists, with Southwest, South, Central, Northeast, and Northwest regions showing negative net effects, while North and East China exhibit positive effects. The findings suggest the need for differentiated regional policies and targeted agricultural emission reduction strategies to achieve China's agricultural “dual carbon” goals.